Shallow magma chamber under the Wudalianchi Volcanic Field unveiled by seismic imaging with dense array - Zhiwei Li; Sidao Ni; Baolong Zhang; Feng Bao; Senqi Zhang; Yang Deng; David A. Yuen (Geophysical Research Letters)
Abstract The Wudalianchi Volcano Field (WDF) is a typical intraplate volcano in northeast China with generation mechanism not yet well understood. As its last eruption was around 300 years ago, the present risk for volcano eruption is of particular public interest. We have carried out a high‐resolution ambient noise tomography to investigate the location of magma chambers beneath the volcanic cones with a dense seismic array of 43 seismometers and ~ 6 km spatial interval. Significant low‐velocity anomalies up to 10% are found at 7–13 km depth under the Weishan volcano, consistent with the pronounced high electrical‐conductivity anomalies from previous magnetotelluric survey. We propose these extremely low velocity anomalies can be interpreted as partial melting in a shallow magma chamber with volume at least 200 km3 which may be responsible for most of the recent volcanic eruptions in WDF. Therefore, this magma chamber may pose a serious hazard for northeast China.